Evaluation of electronic toll collection along South Luzon Expressway and Manila Skyway - Padayhag, Grace U. (2002)
Electronic Toll Collection (ETC) system in different countries has different operating characteristics. In this paper, the operational evaluation of the local ETC system, which was launched in August 2000, was being conducted primarily through video survey depicting the traffic condition of the selected toll plazas. The overall aim of the study is to determine the service rate of vehicles that passed through a toll plaza, comparing the manual, mixed mode and dedicated ETC collecting tollbooths. The results of the analysis show that the dedicated E-pass lane has a lesser tollbooth transaction time with an average service time of 1.15 seconds/vehicle. However, usage of an E-pass lane was not maximized because, in spite the speedy transaction, more motorists pass through the conventional scheme, which is, paying tolls in cash coupons. This manual scheme has a slower average service time rate of approximately 15 seconds/vehicle that causes the vehicles to spill over the plaza. The mixed-mode, serving the manual and ETC scheme, lane is fairly slower than the exclusive E-pass lane, which has a service time rate of approximately 5.5 seconds/vehicle. Based on these results it can be concluded that the dedicated E-pass lane is faster in tollbooth transaction than that of the manual and mixed-mode scheme. Furthermore, lane capacity and delay of each toll-lane also vary widely with the type of toll-collecting booths. On the other hand, the queue delay in mixed-mode scheme is significantly less that for purely manual scheme.